Evaluation of Changes of Kidney Parameteres in New Zealand Rabbits Subsequent to 90 Days Exposure to Uranyl Nitrate in Drinking Water - A Mahmoudzadeh; E Javadi; Z Mohseni (Tehran University of Medical Sciences, 2007)
Background: This study was undertaken to examine the reversibility of renal injury in the male New Zealand white rabbits subsequent to a 90-days exposure to uranyl nitrate (UN) in drinking water. Animals were exposed for 90 days to uranyl nitrate in their drinking water (24 or 500mg/l). Control group were given municipal tap water. Methods: The indicators of kidney function measured in this study included glucose (marker of tubular) microalbumin(marker of glomerular) and marker for cell toxicity was  alkaline phosphatase. Results: Urinary glucose was found to be significantly different and positively correlated with uranium intake for rabbits. Microalbuminuria was found to be significantly different but this different is in normal range. Increase of alkaline phosphatase at weeks 2, 4, 6 was correlated with uranium intake, but at weeks 8, 10, 13 excretion of alkaline phosphatase was decreased. Conclusion: These results suggest that chronic ingestion of uranium in drinking water affect kidney function and to the proximal tubule, rather than glomerul.